TALK SHOWISU PUBLIK DI TELEVISI DAN DINAMIKA DEMOKRASI - Udi Rusadi (BPSDMP Kominfo Jakarta, 2012)
This article describes the audience responses to the role of television talk show participants and their implications for the dynamics of democracy. The article is written based on a audience survey to the talk show Apa khabar Indonesia Malam in TVone. Survey is conducted in the city of Banjarmasin, South Kalimantan. The research findings show, guestoften emphaisizing self-interest and group and often to give emotional statement. Host has demonstrated its role as a moderator as well as provocateur, trying to dig up and dvelop the conflict as a commodity of media content. Under these conditions confirmed the view that the public sphere as a pillar of democratic played hard by mass media. Artikel ini menggambarkan tanggapan khalayak terhadap peran partisipan talk show televisi dan implikasinya terhadap dinamika demokrasi. Tulisan didasarkan pada hasil survey tanggapan penonton terhadap talk show Apa khabar Indonesia Malam di TVone. Lokasi survey di wilayah kota Banjarmasin, Kalimantan Selatan. Temuan penelitian menunjukkan, nara sumber talk showdirespon penonton sering menonjolkan kepentingan diri dan kelompoknya serta pernyataannya sering emosional. Host telah menunjukkan peranannya sebagai moderator sekaligus provokator, berusaha menggali konflik sebagai komoditas isi media. Kondisi tersebut mengukuhkan pandangan bahwa public spheresebagai pilar demokrasi sulit diperankan media massa.